2006
DOI: 10.1021/jf061921h
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Recombinant Dog Gastric Lipase from Transgenic Corn Seed

Abstract: Several approaches were examined for extracting the relatively hydrophobic protein recombinant dog gastric lipase (rDGL) expressed in the endosperm of transgenic corn seed. The first approach used minimal processing of the seed before extraction (i.e. simple grinding of whole seed) followed by selective extraction to eliminate 72% of contaminant proteins without compromising rDGL recovery from the meal of whole grain. The second approach added defatting of the whole grain meal to reduce the amount of detergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…in the production of lipases. 15 Well-established dry-and wet-milling processes have been utilized by milling industries to fractionate corn components for value-added products, but they have not been extensively studied to fractionate corn as a means to enrich recombinant proteins. Only a few studies on the dry-milling process for that purpose have been published 7,13 and no extensive study on the fractionation efficiency of the wet-milling process for the recovery of recombinant proteins could be identified.…”
Section: Introductionmentioning
confidence: 99%
“…in the production of lipases. 15 Well-established dry-and wet-milling processes have been utilized by milling industries to fractionate corn components for value-added products, but they have not been extensively studied to fractionate corn as a means to enrich recombinant proteins. Only a few studies on the dry-milling process for that purpose have been published 7,13 and no extensive study on the fractionation efficiency of the wet-milling process for the recovery of recombinant proteins could be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Most grain fractionation processes for recovery of recombinant proteins produced in maize have been based mainly on hand separation or drymilling procedures. 12,15,20,26,27,34 On the other hand, an early preliminary study on fractionation of transgenic maize producing b-glucuronidase (GUS) by wet-milling showed detrimental effects on recombinant GUS activity. 27 In order to study the effects of the steeping composition on LT-B recovery from wet-milled fractions, we carried out the milling process using traditional (SO 2 þ lactic acid, TS) and water steeping (WS).…”
Section: Resultsmentioning
confidence: 99%
“…25 Standard dry-milling procedures were also used to study the benefit of fractionation in purification of a recombinant dog lipase targeted to be expressed in the endosperm of transgenic maize. 20 In this study, it was reported that recombinant lipase can be extracted from both endosperm and germ fractions, but utilization of endosperm fraction can eliminate the need for germ defatting and its effects on recombinant protein purification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations